The Importance Of Litho-Facies Distinction In Determining The Most Representative Cementation Factors For Well-Log Evaluation : An Old Issue Persistently Neglected - Bambang Widarsono (Testing Center for Oil and Gas LEMIGAS, 2011)
Cementation factor is a parameter always required in any conventional open-hole log analysis leading to determination of water saturation. Considering the central of water saturation in the estimation of hydrocarbon in place and reserves, any error in the use of the parameter may prove fatal. A common practice in the oil industry is that acquisition of laboratory-derived cementation factor has never been given a proper attention. It occurs very often that too few samples – hardly represent the rocks of reservoir of concern – are assigned for laboratory test. The practical use of the parameter in the log analysis also often draw question, in which un-representative cementation factor is arbitrarily used due to lack of the data. The effect of this practice has long been known but is often neglected – with all of its consequences – up to present day. This study tries to revive the awareness through presenting a fact that cementation factor may vary due to differences in litho-facies characteristics. Formation resistivity factor data from forty-seven limestone coreplug samples were taken from a West Java (WJ) field. Visual description over the samples has shown that they belong to several litho-facies types. Results of the study have mainly proved that different litho-facies type may have significantly different cementation factors. An averaging effect is also obvious when data from all samples are processed collectively. The effect of improper use of cementation factor is shown through the application of three water saturation models through which erroneous water saturation estimates are produced. The finding of the study is again hoped to reinforce the awareness of the use of proper and representative cementation factor